2012
DOI: 10.1161/circulationaha.112.126144
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Comparison of Sevoflurane Versus Propofol to Reduce Perioperative Myocardial Ischemia in Patients Undergoing Noncardiac Surgery

Abstract: Background-Volatile anesthetics provide myocardial preconditioning in coronary surgery patients. We hypothesized that sevoflurane compared with propofol reduces the incidence of myocardial ischemia in patients undergoing major noncardiac surgery. Methods and Results-We enrolled 385 patients at cardiovascular risk in 3 centers. Patients were randomized to maintenance of anesthesia with sevoflurane or propofol. We recorded continuous ECG for 48 hours perioperatively, measured troponin T and N-terminal prohormone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(39 citation statements)
references
References 55 publications
(56 reference statements)
1
38
0
Order By: Relevance
“…However, major adverse cardiac events occurred in only 8 % [11]. A large study in patients with atherosclerosis or at risk for it undergoing non-cardiac surgery found myocardial infarction in 5 % and troponin release in 8 % of patients [12].…”
Section: Discussionmentioning
confidence: 99%
“…However, major adverse cardiac events occurred in only 8 % [11]. A large study in patients with atherosclerosis or at risk for it undergoing non-cardiac surgery found myocardial infarction in 5 % and troponin release in 8 % of patients [12].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of lower pretest endtidal sevoflurane concentrations in nonsurvivors—despite of higher epinephrine and norepinephrine plasma concentrations—remains unclear. It could be hypothesized that they were ‘weaker’ animals or had reduced organ protection by sevoflurane, whereas the latter is controversially debated in the literature . On the other side, it is unclear why ‘weaker’ animals should have longer times from apnea until circulatory arrest.…”
Section: Discussionmentioning
confidence: 99%
“…Another area of interest is whether particular medications are more likely to cause postoperative delirium. A recent RCT comparing maintenance of anesthesia with sevoflurane or propofol found no difference in the incidence of delirium between the two groups [79]. Radtke and coauthors found the intraoperative use of fentanyl, as opposed to remifentanil, to be an independent predictive factor for POD [31].…”
Section: Noncardiac Surgerymentioning
confidence: 99%